Comparative Proteome Identifies Complement Component 3-Mediated Immune Response as Key Difference of Colon Adenocarcinoma and Rectal Adenocarcinoma - Liang, Jun-Ze; Liang, Xiao-Ling; Zhong, Li-Ye; Wu, Chu-Tian; Zhang, Jing; Wang, Yang (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most lethal diseases with high morbidity and mortality worldwide. Clinically, tumors located in colon and rectum have diverse prognosis and therapeutic outcome. Here, we performed data mining derived from 20 CRC patient samples to compare proteomic difference between colon adenocarcinoma (COAD) and rectal adenocarcinoma (READ). We found that differential expressed proteins (DEPs) upregulated in COAD were mainly enriched in immune response, moreover, higher immune scores were found in COAD than READ, as calculated by The Cancer Genome Atlas (TCGA) data. To identify the core protein of DEPs with high prognostic value for COAD, we performed topological overlap matrix (TOM) to investigate the hub proteins using 77 immune-relevant DEPs. The results showed that complement component 3 (C3) as the core protein in the immune-relevant DEPs matrix between the COAD and READ. Moreover, we found that C3 was up-regulated in COAD, and its expression was negatively associated with overall survival of COAD patients but not READ. In conclusion, we identified C3-mediated immune response as key feature for distinguishing COAD and READ, and highlighted C3 as potential biomarker with high prognostic value for clinical application, which provided new clue for precise treatment of COAD.